Effectiveness of rebozo and birth ball techniques on labour pain at First stage - Asry, Sari Angan; Mujahidah, Sa'adah; Wulandari, Dyah Ayu; Mayangsari, Dewi (CV LINK Education Publication, 2024)
Introduction: Labor pain is a natural phenomenon experienced by every mother during birth. Improperly controlled pain will affect the labor process. Rebozo and birth ball procedures are non-pharmacological approaches employed to alleviate labor pain. Objectives: The study’s aimed to ascertain the differential efficacy of rebozo and birth ball treatments on labor pain during the first stage. Methods: This research constitutes a quasi-experiment using a two-group pretest and posttest design. The population comprised 106 everyday birth moms in Purwoharjo Health Centre, Pemalang Regency, from December 2021 to January 2022. Data gathering methods incorporated observational techniques and the NRS scale instruments and employed the Wilcoxon and Mann-Whitney tests. Results The rebozo technique can diminish labor pain intensity by 1.72 points, while the birthing ball approach can decrease it by 2.36 points. The Mann-Whitney test results indicated a significant difference in the efficacy of the rebozo and birth ball approaches on first-stage labor pain, with a p-value of 0.023. Conclusion: The birth ball technique is more efficacious in alleviating labor pain. Midwives are advised to employ the birth ball technique as a non-pharmacological approach to relieve labor pain.